Cover Image. Issue 5 (21st October 2020) - Okuda, Itsuko; Yamakawa, Yumika; Mitani, Nobu; Ota, Naoko; Kawabata, Marie; Yoshioka, Naoki
Abstract : The cover image is based on the Original Article Objective evaluation of the relationship between facial expression analysis by the facial action coding system (FACS) and CT/MRI analyses of the facial expression muscles by Itsuko Okuda et al., https://doi.org/10.1111/srt.12864 .